Literature and social reform in colonial Orissa : the legacy of Sailabala Das (1875-1968) - Dāsa, Śaiḷabāḷa (Sahitya Akademi, 2006)
Introduction : the legacy of Sailabala Das / by Sachidananda Mohanty -- From Bilāt prabās = Journey to England (originally in Oriya) / by Sailabala Das -- Ways of spreading women's education (originally in Oriya) / by Sailabala Das -- From A look before and after! (Originally in English) / by Sailabala Das